2015
DOI: 10.1186/s12936-015-0702-7
|View full text |Cite
|
Sign up to set email alerts
|

Is there a distinction between malaria treatment and intermittent preventive treatment? Insights from a cross-sectional study of anti-malarial drug use among Ugandan pregnant women

Abstract: BackgroundIn Uganda, treatment of clinical malaria and intermittent preventive treatment with sulphadoxine-pyrimethamine (SP) are common during pregnancy. As a result, both formal and informal reports from antenatal sources suggest possible misuse of SP for malaria treatment among pregnant women. The objective of this study was to investigate anti-malarial drug use patterns among women who had recently suffered malaria illness before and during pregnancy.MethodsA cross-sectional study in which a structured que… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 26 publications
1
5
0
Order By: Relevance
“…Considering that women aged between 15–49 years represent around 25.0% of the total population [ 43 ], one would expect around 2.0% of the participants to have SP in their blood, much lower than the proportion measured in our study. As mentioned before, this large discrepancy goes in line with previous studies reporting the common use of SP as self-medication [ 11 , 22 , 44 ]. Measuring SP in the blood provides interesting insight on how these treatments are used in different regions of the country and by different population groups.…”
Section: Discussionsupporting
confidence: 88%
“…Considering that women aged between 15–49 years represent around 25.0% of the total population [ 43 ], one would expect around 2.0% of the participants to have SP in their blood, much lower than the proportion measured in our study. As mentioned before, this large discrepancy goes in line with previous studies reporting the common use of SP as self-medication [ 11 , 22 , 44 ]. Measuring SP in the blood provides interesting insight on how these treatments are used in different regions of the country and by different population groups.…”
Section: Discussionsupporting
confidence: 88%
“…A nationally-representative survey of health facilities found that over 90 % of facilities in Uganda had sulfadoxine/pyrimethamine in stock in 2012 [ 67 ], indicating that stock-outs were an unlikely root cause of low IPTp2. Previous work suggests that prescription practices by health providers, including the misuse of sulfadoxine/pyrimethamine to treat clinical malaria, may be the main driver of low rates of IPTp [ 77 , 78 ]. Further examination is needed to identify and address the factors leading to low IPTp2 coverage throughout Uganda.…”
Section: Discussionmentioning
confidence: 99%
“…Where no effort is made to ascertain actual user compliance, such findings remain questionable, especially coming from resource-constrained settings where unsupervised administration of SP is the norm, contrary to guidelines. As argued elsewhere, the presence of such records does not necessarily translate into intake compliance [21, 22]. Our findings are however limited by the small sample sizes used that may not be adequately powered to detect true differences between the groups.…”
Section: Discussionmentioning
confidence: 76%
“…However, such findings in most cases are hampered by the exclusive reliance on self-reports and antenatal records to ascertain SP use. Because unsupervised SP-IPTp administration is a common occurrence in many resource-limited settings, we have previously argued that self-reports and ANC records may not necessarily translate into SP intake compliance [21, 22]. Moreover, where intake was ascertainable, studies have continued to show effectiveness of SP-IPTp [13, 2329].…”
Section: Introductionmentioning
confidence: 99%